A diplomacy of the oppressed: New directions in international feminism - Ashworth, Georgina (Zed Books, 1995)
Les contributrices abordent les problèmes du mouvement international des femmes, tels que la résolution des conflits; la violence; zones de libre-échange ; l'environnement; culture et identité nationale; santé; les média; droits humains; et l'emploi, en mettant l'accent sur la situation des femmes dans toutes les régions du monde. Destiné aux étudiants en études féministes, en sciences politiques et en études du développement
Keywords: 1900-1999; anthologie; approches et analyses; conflit; coopérative internationale; cours; discipline; fem1000; genre; histoire; histoire et politique; identités LGBTQIA2+; inégalités; militance; mouvements des femmes*; mouvements féministes; premier cycle; périodes historiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques

America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Mapping desire: geographies of sexualities - Bell, David; Valentine, Gill (Routledge, 1995)
This is the first book to explore sexualities from a geographical perspective. The nature of place and notions of space are of increasing centrality to cultural and social theory. Mapping Desire presents the rich and diverse world of contemporary sexuality, exploring how the heterosexual body has been appropriated and resisted on the individual, community and city scales. The geographies presented here range across Europe, America, Australasia, Africa, the Pacific and the imaginary, cutting across city and country and analysing the positions of gay men, lesbians, bisexuals and heterosexuals. The contributors ring different interests and approaches to bear on theoretical and empirical material from a wide range of sources. The book is divided into four sections: cartographies/identities; sexualised spaces: global/local; sexualised spaces: local/global; sites of resistance. Each section is separately introduced. Beyond the bibliography, an annotated guide to further reading is also provided to help the reader map their own way through the literature.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; géographie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques

L’éducation des enfants dans Le Chrysanthème et le sabre - Benedict, Ruth Fulton; Mécréant, Lise (Le Chrysanthème et le sabre, 1995)
Cet essai, écrit à distance, sur commande de l'Office of War Information, par une femme qui n'était jamais allée au Japon et en ignorait la langue, pour servir de manuel aux forces d'occupation américaines, réussit la gageure de demeurer, de l'avis général des Japonais, l'un des grands livres que l'on ait écrit sur eux. Des articles et des ouvrages ont, après lui, été publiés qui réfutent, complètent, approfondissent, réapprécient les interprétations de Ruth Benedict. Ces débats lui ont conféré la place d'une référence classique." Ce livre traite des habitudes qui paraissent naturelles et que nul ne songerait à remettre en cause au Japon. Il traite des situations où tout Japonais peut compter sur la courtoisie et de celles où il se sent honteux, des circonstances où il éprouve de l'embarras, de ce qu'il exige de lui-même." On y parle des règles de hiérarchie, de bienséance, de l'éducation des enfants, de morale sexuelle, de politique économique ...
Keywords: 1900-1999; 1990-1999; approches et analyses; asie; cours; discipline; japon; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; thématiques

Les relations amoureuses entre les femmes du XVIe au XXe siècle. Essai historique. - Bonnet, Marie-Joe (Opus, 1995)
Voici la première histoire de l'amour entre les femmes qui, sur cinq siècles, de la Renaissance à nos jours, tienne compte à la fois du regard extérieur des hommes et de l'approche des lesbiennes elles-mêmes. Pour la première fois, aussi, une analyse à long terme est proposée qui dégage une évolution des moeurs, des mentalités et de la place des femmes dans la société. Jusqu'à présent, en effet, l'histoire des femmes occultait l'amour entre femmes, alors que les lesbiennes ont joué un rôle prépondérant dans les mouvements progressistes politiques et artistiques. Unique en son genre par son érudition, son approche pluridisciplinaire, ses mises en perspective originales et la période considérée, cet essai s'impose déjà comme un ouvrage de référence.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; droits des femmes*; europe; fem1000; fem7000; france; histoire; histoire des femmes*; histoire et politique; hétérosexisme; identités; identités LGBTQIA2+; invisibilités; lesbianisme; lit3220; premier cycle; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Gender articulated: language and the socially constructed self - Hall, Kira; Bucholtz, Mary (Routledge, 1995)
Gender Articulated is a groundbreaking work of sociolinguistics that forges new connections between language-related fields and feminist theory. Refuting apolitical, essentialist perspectives on language and gender, the essays presented here examine a range of cultures, languages and settings. They explicitly connect feminist theory to language research. Some of the most distinguished scholars working in the field of language and gender today discuss such topics as Japanese women's appropriation of "men's language," the literary representation of lesbian discourse, the silencing of women on the Internet, cultural mediation and Spanish use at New Mexican weddings and the uses of silence in the Anita Hill-Clarence Thomas hearings.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; maternité; premier cycle; queer; sciences humaines; sociolinguistique; thématiques; études de genres